Biological and mechanical challenges in the endodontic treatment of immature teeth with pulp necrosis: insights based on a Series of Atypical Clinical Cases - Julian Gregoire Leprince; Motoki Okamoto; Matthias Widbiller; Julien Beauquis; Simon Mariano Pedano; Kerstin M. Galler; Yusuke Takahashi (Biomaterial Investigations in Dentistry)
Over the past two decades, dental pulp regeneration has become a major focus in endodontology. The currently applied clinical strategies are referred to as ‘revitalisation’ procedures. These biology-based treatment strategies aim at regenerating lost pulp tissues in necrotic teeth, in the absence or even more in the presence of periapical bone lesion, clinical signs and symptoms. Such approaches are generally – but not exclusively – used in immature teeth to promote root maturation, both in length and in thickness, ultimately to reduce their risk of fracture. A growing body of evidence has led to increased understanding and reliability of these treatment strategies, which are now considered as a valid alternative treatment option besides conventional ones, mainly the apical plug technique. However, all systematic reviews evaluating clinical outcomes concluded that there is a lack of robust long-term studies on the subject; most published cases of revitalisation having a relatively short-term follow-up, usually under 2 years. In this context, several major challenges remain to be addressed to better understand the promises and limitations of revitalisation procedures as compared to other treatment options, mainly the placement of an apical plug made of hydraulic calcium silicate cement. The purpose of this paper was therefore to identify some of the important remaining challenges related to such procedures, which can be broadly categorised into biological and mechanical ones, affecting treatment success and tooth survival. Meeting these challenges requires close collaboration between both researchers and clinicians, to establish guidelines, evaluate and understand treatment outcomes, and update guidelines accordingly. However, it is not always easy for researchers to understand the clinical reality faced by practitioners. In order to facilitate their mutual understanding, the aforementioned challenges were illustrated by providing clinical context through a series of atypical clinical cases with long-term follow-up (4–8 years).